Women with exposure to childhood interpersonal violence without psychiatric diagnoses show no signs of impairment in general functioning, quality of life and sexuality. Issue 1 (December 2016) - Rausch, Sophie; Herzog, Julia; Thome, Janine; Ludäscher, Petra; Müller-Engelmann, Meike; Steil, Regina; Priebe, Kathlen; Fydrich, Thomas; Kleindienst, Nikolaus
Abstract Background Childhood interpersonal violence is a major risk factor for developing Posttraumatic Stress Disorder (PTSD), other axis-I disorders or Borderline Personality Disorder (BPD). Individuals with a history of childhood sexual abuse (CSA) and childhood physical abuse (CPA) who meet the criteria of any axis-I disorder usually also exhibit general psychopathologic symptoms and impairments in quality of life and sexuality. The present study investigates whether women with a history of potentially traumatic CSA/CPA without any axis-I disorder or BPD show subthreshold symptoms of PTSD-specific and general psychopathology and impairments in global functioning, quality of life, and sexuality. Methods Data were obtained fromN = 92 female participants:n = 31 participants with a history of potentially traumatic CSA/CPA (defined as fulfilling PTSD criterion A) without any axis-I disorder or BPD;n = 31 participants with PTSD related to CSA/CPA; andn = 30 healthy controls without any traumatic experiences. All three groups were matched for age and education. Those with a history of CSA/CPA with and without PTSD were further matched with regard to severity of physical and sexual abuse. Results While women with a history of potentially traumatic CSA/CPA without axis-I disorder or BPD clearly differed from the PTSD-group in the collected measures, they did not differ from healthy controls (e.g., GAF:87, BSI:0.3, BDI-II:4.5). They showed neither PTSD-specific nor general subthreshold symptoms nor any measurable restrictions in quality of life or sexual satisfaction. Conclusions Women with a history of potentially traumatic childhood interpersonal violence without axis-I disorder or BPD show a high level of functioning and a low level of pathological impairment that are comparable to the level of healthy controls. Further studies are needed to identify what helped these women survive these potentially traumatic experiences without developing any mental disorders. Trial registration German Clinical Trials Registration ID:DRKS00006095 . Registered 21 May 2014.